Green synthesis of Silver oxide nanoparticles using Zephyranthes Rosea flower extract and evaluation of biological activities. Issue 5 (October 2020) - Maheshwaran, G.; Nivedhitha Bharathi, A.; Malai Selvi, M.; Krishna Kumar, M.; Mohan Kumar, R.; Sudhahar, S.
Graphical abstract: Highlights: Ag2 O NPs were synthesized by greener method using Zephyrathes Rosea flower extract. Optical absorption peak of Ag2 O NPs was observed at 420 nm and the band gap energy was 2.48 eV. Ag2 O NPs has spherical morphology with particle size in the range of 10−30 nm. It is found that, Ag2 O NPs exhibits very good anti-bacterial, anti-inflammatory activities. Abstract: Bio-nanotechnology is an effective technique for the synthesis of nanoparticles in a greener approach without affecting the environment. The present research provides the in-vitro synthesis of Zephyranthes Rosea flower extract substituted silver oxide nanoparticles by a greener approach for the first time. The formation of the face centered cubic structure of Ag2 O NPs was confirmed by X-ray diffraction (XRD) pattern. The synthesized nanoparticles were characterized by X-ray Photoelectron Spectroscopy (XPS) analysis to confirm the chemical states and purity of Ag and O. The optical absorption peak of the nanoparticle was found to be at 420 nm and optical emission peaks were observed at 412 nm, 485 nm, and 530 nm. The bandgap energy of the Ag2 O NPs was found to be 2.48 eV. The morphology of the nanoparticles was found to be spherical with the particle size about 10−30 nm and the lattice inter-planar spacing was found to be 0.222 nm. Ag2 O NPs Zephyranthes Rosea were found to be a potential candidate for the antibacterial activity against the strains of E scherichia coli, Streptococcus mutants, and Staphylococcus aureus . The antioxidant activity of Ag2 O NPs was found to be 73.82 % at 100 μg/mL with the standard drug of ascorbic acid. The anti-inflammatory activity of the Ag2 O NPs was found to be 97.19 % at 500 μg/mL using the BSA denaturation technique. The anti-diabetic activity of the Ag2 O NPs was tested by α-amylase assay and the inhibition percentage was found to be 75.7 % at 500 μg/mL.